On the question of microbial cenoses of fish and the role of microorganisms of the genus Bacillus under herbicidal water pollution - Barbukho, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Substantial reduction in the number of Bacillus as part of microbocenosis of fish intestines, skin and gills at different level of toxicity of the environment caused by pollution with glyphosate has been detected and their indicator significance has been determined. Correlation analysis has been done, which showed that the most close relationship between the concentration of glyphosate in water and the number of Bacillus cells as a part of fish microflora is typical for the skin and gills of carp, and therefore in order to assess the level of toxic contamination of hydroecosystems it’s appropriate to use these tissues. As a result of regression analysis, regression models are presented, and in particular a multiple regression model with two independent variables, that allow to predict the concentration of glyphosate in water by experimentally established Bacillus cell number in these tissues. Proposed models can be used to establish herbicidal water pollution, in particular for calculation of the amount of glyphosate in water in conditions of aquarium fish keeping and if all the factors that may affect the number of bacteria correspond with conditions of experiment. Authors have proposed to use genus Bacillus microorganisms on the skin and gills of fish as an indicator for the diagnosis of toxicological situation in the reservoirs.